Curriculum Analysis of Food Safety Competences at Elementary and Upper‐Secondary Level of Formal Education Inside Food‐Related Programs in Slovenia. Issue 2 (16th April 2018) - Ovca, Andrej; Jevšnik, Mojca; Raspor, Peter
Abstract: Since formal education is guided through food‐related curricula, there is a concern regarding to which extent food safety elements are supported in the current educational objectives presented in syllabi. The aim of this study was to analyze the existing food safety elements in the syllabi at the elementary (for students between 6 and 14 y of age) and upper‐secondary level (food‐related programs) of formal education (for students between 15 and 18 y of age). Analysis was done through predefined criteria, evaluating the educational objectives listed in available syllabi approved by the national government. The results revealed the elementary level as a good prestage for education at the next level concerning food safety elements. At the upper‐secondary level, the acquisition of knowledge and development of skills related to food safety elements of interest are well supported. However, based on frequent errors made by professional food handlers reported in the literature, the role of food handlers and their food safety awareness should receive more attention in the syllabi. To support this and to overcome a lack of educational objectives identified, several actions are suggested. Based on methodological recommendations for the teacher in the syllabi, the importance of qualified teachers was once again confirmed. Vocational schools are and will remain an indispensable pillar in the education of future professional food handlers; however, teachers with sufficient knowledge and a positive attitude toward food safety seems to be, besides quality curricula, one of the important factors in achieving the proper attitudes of people required to implement food safety.